The impact of accessing education via smartphone technology on education disparity—a sustainable education perspective - Alam, Gazi Mahabubul; Forhad, Md. Abdur Rahman (Multidisciplinary Digital Publishing Institute, 2023)
Following the fourth target of the United Nations’ Sustainable Development Goals (SDGs), education disparity is one of the graver concerns delaying substantial economic development, especially in emerging market-based nations. Despite numerous efforts to address this disparity, it has been a long-standing concern for many communities. It is important to note that the recent pandemic has changed teaching and learning approaches worldwide, where disparity is one of the most challenging issues. Although similar and/or equal access to technology has always been challenging, online learning practices were widely implemented with varying levels of success during the pandemic. Using purposive sampling on administrative data between 2020 and 2022 on undergraduate programs in public universities in Bangladesh, this study examines the effects of technology access on academic achievement. This study employs the difference in differences (DID) technique to analyze the data and finds that access to technology improves students’ learning. Findings strongly suggest that technology access reduces disparity, mainly due to socioeconomic status (SES). Findings also imply that ensuring access to technology for individuals from poorer SES backgrounds should be prioritized to address education inequality-related challenges.